PELATIHAN PENGISIAN SURAT PEMBERITAHUAN (SPT) TAHUNAN PAJAK PENGHASILAN (PPh) BAGI USAHA MIKRO KECIL MENENGAH (UMKM) DI KOTA SEMARANG - Anita Damajanti; Yulianti Yulianti; Sudarmin Sudarmin (Publisher UPT P2M Politeknik Negeri Malang, 2019)
Annual Income Tax Return is a means used to report income tax that has been paid by taxpayers for one year. The form used to report the Annual Income Tax Return for individual taxpayers who have business activities that are classified as Micro, Small and Medium Enterprises (MSMEs) is the Annual Tax Return form 1770. Completion of the Annual Income Tax Return form is still difficult for MSMEs, especially newly registered taxpayers who do not understand taxation terms. This community service activity aims to provide guidance and training for MSMEs in filling the Annual Income Tax Return form. This community service activity was held at the Faculty of Economics, University of Semarang. The target audience is the MSMEs community in Semarang City. There were 20 MSMEs who attended this event. The event held on March 24, 2019. The method of carrying out the activity is the presentation and the simulation of filling Annual Tax Returns for MSMEs.The results of this activity showed that participants were able to fill in the 1770 Annual SPT form. Participants expect similar activities to be carried out in the coming period.